Comparative Analysis of Cash Receipts Accounting Systems at South Bengkulu's Aldi Cell Counter - Aresman, Ronaldi; Anggriani , Ida; Noviantoro , Rinto (Universitas Dehasen Bengkulu, 2022)
A trading company is a company whose main activity is selling merchandise directly to consumers. The system for selling merchandise must have a good recording system, namely the company's internal control system can oversee all these activities. The internal control system is a tool to oversee every activity carried out by the company to protect the company's assets. The purpose of this study was to determine the cash receipts accounting system at the South Bengkulu Aldi Cell Counter. The analytical method in this study uses comparative analysis. The results of the study show that cash receipts from cash sales at the Aldi Cell Counter in South Bengkulu, seen from the related functions, are in accordance with the theory put forward by Mulyadi. Where conformity is found in the sales function, cash function and bookkeeping function. Meanwhile, there is a discrepancy in the delivery function, because all purchase transactions are carried out on-site (offline). There is a discrepancy in the accounting records used in cash receipts from cash sales because they only use simple bookkeeping records. In the documents used in cash receipts from cash sales, conformity is found in the documents used and the recap of the cost of goods sold in the form of recording the bookkeeping of goods. Meanwhile, there is a discrepancy in the proof of bank deposit, because the proceeds from the sale of goods were not deposited into the bank, but were used to purchase more goods. The calculations made by Tempe Silvia did not take into account factory overhead costs.